2022
DOI: 10.1111/all.15538
|View full text |Cite
|
Sign up to set email alerts
|

Delayed type hypersensitivity reactions to various allergens may differently model inflammatory skin diseases

Abstract: Background: Treatment of inflammatory skin diseases, including atopic dermatitis (AD) and psoriasis, is undergoing transformative changes, highlighting the need to develop experimental models of skin inflammation in humans to predict treatment responses. Methods:We topically or intradermally administered four common sensitizers (dust mite (DM), diphencyprone (DPCP), nickel (Ni), and purified protein derivative (PPD)) to the backs of 40 healthy patients and the skin hypersensitivity response was biopsied and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 70 publications
7
12
0
Order By: Relevance
“…DPCP had the highest cell infiltration and elicited a strong multipolar Th1/ Th2/Th17 and Tc1 inflammatory profile when compared to the other contact sensitizers. These observations corroborate the molecular study in the clinical trial which showed that DPCP induced a broad polarization signature 16. The bulk RNA-seq molecular study provides an overall Type 1, Type 2, and/or Type 17 polarization in terms of cytokines, chemokines and their receptors, transcription factors and innate immune signatures as well as changes in barrier differentiation genes for the four sensitizers 16.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…DPCP had the highest cell infiltration and elicited a strong multipolar Th1/ Th2/Th17 and Tc1 inflammatory profile when compared to the other contact sensitizers. These observations corroborate the molecular study in the clinical trial which showed that DPCP induced a broad polarization signature 16. The bulk RNA-seq molecular study provides an overall Type 1, Type 2, and/or Type 17 polarization in terms of cytokines, chemokines and their receptors, transcription factors and innate immune signatures as well as changes in barrier differentiation genes for the four sensitizers 16.…”
supporting
confidence: 83%
“…Lack of access to allergen unexposed skin biopsies from allergensensitized healthy volunteers for flow cytometry as compared to the molecular arm of the study, 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD3 + T-cells, CD11c + myeloid dendritic cells (DC), DC lysosomal associated membrane glycoprotein (DC-LAMP) + mature DCs, myelin basic protein (MBP) + eosinophils and forkhead box P3 (FOXP3) + T regulatory cells (Tregs) were significantly enriched. Ni application caused barrier defects by reduction of terminal differentiation (filaggrin (FLG), FLG2, loricrin (LOR), and late cornified envelope proteins (LCEs)), tight junction (claudin (CLDN)1/CLDN8), and lipid metabolism (fatty acid 2-hydroxylase (FA2H), fatty acid binding protein 7, brain (FABP7)) AD-related markers [ 73 ]. After positive Ni-PT, skin biopsies were taken at different time points (0 to 96 h).…”
Section: Mechanisms and Biomarkersmentioning
confidence: 99%
“… Outcomes Exposition to Metal Ref. ↑ metal-specific CD154 + CD4 + Tmem (overexpression of TRAV9-2 and CDR3 histidine) Allergic and non-allergic subjects stimulated with Ni, Co or Pd (PBMC) [ 67 , 68 ] ↑ IL-5 Ni-allergic patients (PBMC) [ 69 ] Ni-allergy patients, differentiation between independent Ni or cross-reactivity of Ni/Pd allergy (PBMC) [ 71 ] Cross reactivity between Ni/Cr and Pd Sensitization with Ni or Cr, challenge with Pd (mice model) [ 70 ] Skin barrier defects: ↓ terminal differentiation—FLG, FLG2, LOR, LCEs, tight junction—CLDN1/CLDN8, lipid metabolism—FA2H, FABP7 Biopsies from healthy subjects after Ni-topical application [ 73 ] Cellular infiltrates: ↑ CD3 + T, CD11c + myeloid DC, DC-LAMP + mature DC, MBP + eosinophils, FOXP3 + Treg ↑ M1, mast cells, neutrophils, NK, CD4 + Tmem, CD8 + T Biopsies from Ni-allergic patients [ 74 ] ↓ M2, resting mast cells, Tγδ, Treg ↓ SBSN Ni-allergic patients (serum) [ 75 ] ↑ Sema3A (activates MAPK and TNF-α) Ni-induced allergy (mouse ear tissue) [ 76 ...…”
Section: Mechanisms and Biomarkersmentioning
confidence: 99%